Implementasi Terapi Bermain Lego pada Pasien Anak Usia Pra Sekolah yang Menjalani Hospitalisasi dengan Masalah Kecemasan - Woran, Develin (Yayasan Syalom Cipta Sumikolah, 2025)
Children are individuals who have different characteristics according to their age period. Hospitalization is a condition that requires children to receive treatment in hospital. This can make children afraid, cry, stressed/anxious, and even refuse treatment. One of the impacts of hospitalization is anxiety. Anxiety is the impact of hospitalization experienced by children because they face stressors in the hospital environment. Play therapy is an activity that can be done to get pleasure or satisfaction. Playing can divert pain and provide relaxation to children so that it can relieve tension and stress felt by children. The aim is to obtain